Signaling by underpricing the initial public offerings of primary listings in an emerging market - Aleš Čornanič; Jiří Novák (Charles University in Prague, Institute of Economic Studies (IES), 2013)
The signaling hypothesis suggests that firms have incentives to underprice their initial public offerings (IPOs) to signal their quality to the outside investors and to issue seasoned equity (SEO) at more favorable terms. While the initial empirical evidence on the signaling hypothesis was weak, Francis et al. (2010) show that foreign firms from segmented (rather than integrated) markets strategically underprice their IPO in U.S. markets to distinguish themselves from the weaker players. Hence, the attractiveness of the signaling strategy seems to be related to the a priori level of information asymmetry. We examine the use of signaling in an emerging market where the information asymmetry is likely to be higher relative to an established market. Using a sample of 158 Polish IPOs from 2005 - 2009, we show that firms that underprice their IPOs are more likely (i) to issue seasoned equity, (ii) to issue a larger portion of equity at the SEO, and (iii) to make the SEO sooner after the IPO, all of which are consistent with the signaling hypothesis. This evidence suggests that the results of Francis et al. (2010) are not limited to IPOs made by foreign firms in an established market, but they can be extended to primary listings by domestic firms in markets where the information asymmetry is sufficiently large for the benefit of the signal to outweigh its cost.
Keywords: G14; G15; G30; 330; initial public offering; seasoned equity offering; underpricing; signaling; emerging market; Poland